Rewriting Womanhood : Feminism, Subjectivity, and the Angel of the House in the Latin American Novel, 1887-1903 - LaGreca, Nancy, 1972- (Penn State Romance studies., 2009)
"An historical and theoretical literary study of three Latin American women writers, Refugio Barragán of Mexico, Mercedes Cabello de Carbonera of Peru, and Ana Roque of Puerto Rico. Examines how these novelists subversively rewrote womanhood vis à vis the prescribed comportment for women during a conservative era"--Provided by publisher.